Pengaruh Kecerdasan Emosional Siswa Dan Partisipasi Orang Tua Terhadap Hasil Belajar Siswa SMPN 1 Marioriwawo Kabupaten Soppeng - Megawati, Megawati (Universitas Negeri Makassar, 2018)
In this research there are three problem formulation is (i) whether there is emotional intelligence of students on learning results in social sciences subject (ii) whether there is influence of parents’ participation on learning results in social sciences, (iii) whether there is influence of students’ emotional intelligence and parents’ participation sumultaneously on learning results in social sciences subject in class VIII students at SMPN 1 Marioriwawo in Soppeng district. The type of this study is quantitative. In terms of its purpose, this research is a comparative causal research. The population of the study were all students of class VIII at SMPN I Marioriwawo. The sample selection technique employed cluster random sampling and obtained 90 students as the samples. Data were analyzed by employing descriptive statistics analysis and inferential statistics analysis. The results of tge study reveal that: first, the students’ intelligence gives significant influence on learning results in soscial sciences subject in class VIII students at SMPN 1 Marioriwawo in Soppeng district. Second, parents’ participation gives significant influence on learning results in soscial sciences subject in class VIII students at SMPN 1 Marioriwawo in Soppeng district. Third, the result of simultaneous test indcates that students’ emotional intelligence and parents’ participation give significant influence on learning results.